Combined Use of Rituximab and Intravenous Immunoglobulin for Severe Autoimmune Cicatricial Conjunctivitis—An Interventional Case Series. Issue 12 (December 2016) - Steger, Bernhard; Madhusudan, Savitha; Kaye, Stephen B.; Stylianides, Amira; Romano, Vito; Maqsood, Sundas E.; Harper, Janice; Ahmad, Sajjad
Abstract : Purpose: Despite the availability of systemic immunosuppressants, cicatricial conjunctivitis (CC) remains a potentially blinding ocular surface disease. We aim to describe the combined use of rituximab (RTX) and intravenous immunoglobulin (IVIg) for severe recalcitrant autoimmune CC. Methods: In this single-center retrospective interventional case series with follow-up between 32 and 65 months, 3 cases with mucous membrane pemphigoid (patients 1–3) and 1 case with linear IgA disease (patient 4) were included. Initial conventional immunosuppressive therapy regimens included systemic steroids, dapsone, and mycophenolate. At the time of initiation of RTX and IVIg, all patients had only one eye with good visual acuity or good visual potential. Treatment included 1 to 2 cycles of RTX (1000 mg twice at an interval of 2 weeks apart), and 2 to 9 monthly courses of IVIg (2 g/kg over 3 days). Outcome measures were blindness, as defined by best spectacle-corrected visual acuity <0.05 on a decimal scale, and clinical staging of cicatricial disease (Rowsey and Foster staging). Results: In 4 presented cases, progression of cicatricial disease was stopped as assessed by the Foster grading scale and visual acuity was stabilized in all patients. Conjunctival scarring was stabilized in 2 cases and continued to progress in 2 cases. One patient developed septicemia 6 weeks after RTX infusion, which was successfully treated. Conclusions: Combination therapy of RTX and IVIg is a potent treatment regimen for recalcitrant autoimmune CC. Further prospective controlled studies on efficacy and safety are warranted before widespread clinical application.